Pengaruh Rasio Likuiditas Dan Leverage Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Sub Sektor Industri Makanan Dan Minuman Yang Terdaftar Di BEI - Resa Enjelina Brutu; Mila Yulia Herosian; Bella Christen Panjaitan (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study plans to conclude whether liquidity generally affects industrial points in the Food and Beverage Industry Sub-Area at the Gathering Association written on the IDX. The impact mostly affects organizational points in the Food and Beverage Industry Affiliated Sub-Area listed on the BEI. Liquidity and its utilization after some time basically affect the association points in the Authority Relations of the Food and Beverage Industry Sub-Regional Authority listed on the BEI. The survey approach uses different quantitative tests. The number of examinations in the 2014-2020 investigation period was 11 affiliates. The consequence of this research shows that the liquidity hierarchy in a general sense affects most of the hierarchical qualities in Collector Relations in the Food and Beverage Industry Sub-Regions listed on the IDX. Keywords : Liquidity, Leverage and Firm Value